Lactic acidosis, a potential toxicity from drug–drug interaction related to concomitant ribociclib and metformin in preexisting renal insufficiency: A case report. Issue 8 (5th November 2021) - Lagampan, Chalita; Poovorawan, Nattaya; Parinyanitikul, Napa
Abstract: Background: Ribociclib, one of the cyclin‐dependent kinases (CDK) 4 and 6 inhibitors, in combination with endocrine therapies has been approved in the treatment of hormonal receptor positive, HER‐2 negative metastatic breast cancer worldwide. Long‐term usage of ribociclib with concomitant drugs, potential drug–drug interaction may develop which can limit the therapeutic value of CDK4/6 inhibitor. Case: A 62‐year‐old with history of non‐insulin dependent diabetic, dyslipidemia, and essential hypertension was diagnosed with HR‐positive, HER‐2 negative metastatic breast cancer and treated with fulvestrant plus ribociclib. Four weeks after administration, elevated serum creatinine was observed, and then severe lactic acidosis with acute respiratory failure was subsequently reported. Ribociclib and fulvestrant were temporarily discontinued. Three days after renal replacement therapy, her clinical was stabilized. Combination ribociclib with metformin resulted in high plasma metformin levels and dangerous consequences. Hence, special precaution should be considered during concomitant treatment with sensitive transporter substrates. Conclusion: Metformin associated lactic acidosis may potentially occur after combination with ribocilib, an uncommon but lethal complication from the interaction of these drugs, especially in patients who had preexisting renal impairment.